Asuhan Keperawatan Pada An’ A Dengan Gastroenteritis Akut Berhubungan Dengan Hipovolemia - Dikha Sazilli; Dewi Erna Marisa; Rizki Dian Cahyawati; Mahendra; Sumarni (MEJORA Medical Journal Awatara, 2024)
One of the viral infections that often occurs in children is gastroenteritis or commonly known as Vomiting and Vomiting. Gastroenteritis is medically defined as diarrhea, in other words increased frequency of bowel movements with or without vomiting, fever and abdominal pain. Increased frequency of defecation is defined as ≥ 3 times with watery consistency in 24 hours or at least 200 g of stool/day. This research aims to determine the description of nursing care for pediatric patients with gastroenteritis at Waled Hospital, Cirebon Regency. After applying nursing care to patient A using a case study method consisting of assessment, nursing diagnosis, intervention, implementation and evaluation. The results showed that the diarrhea was resolved with the patient no longer complaining of pain, the pain scale was reduced from 5 – 1, and no issues were found with the patient